Determinan Kepuasan Nasabah KUR Syariah Di BSI Dengan Keputusan Sebagai Variabel Mediasi - Elindahsari, Putri; Adiba, Elfira Maya (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
This study aims to determine the effect of Islamic promotion, Islamic service quality, and trust on customer satisfaction in using KUR financing at BSI with customer decisions as an intervening variable (Study at Bank Syariah Indonesia KCP Sidoarjo Ahmad Yani). This study uses a quantitative approach method. Data collection through questionnaires using a Likert scale. The research sample amounted to 81 using the slovin formula method with mediating variables (intervening). The data was processed using SmartPLS version 4.0. The results showed that Islamic promotion and trust had no significant effect on customer decisions. Islamic service quality has a significant effect on customer decisions. Islamic promotion and customer decisions have no significant effect on customer satisfaction. Islamic service quality and trust have a significant effect on customer satisfaction. While the results of islamic promotion, islamic service quality, and intervening variable trust cannot mediate all.